Monitoring the Convention on Biological Diversity (CBD) framework using evaluation of effectiveness methods. The Italian case. (August 2015) - Marino, D.; Marucci, A.; Palmieri, M.; Gaglioppa, P.
Highlights: We developed a methodology for managing the effectiveness of Italian protected areas. The MEVAP method assesses the environmental performance of protected areas. MEVAP assesses whether protected areas are effective individually and comparatively. We applied the MEVAP method to several clusters of Italian national parks. The MEVAP method achieves adaptive management within protected areas. Abstract: Protected areas play an important role in the preservation and implementation of bold environmental agreements, among which the 20 Aichi Targets (Strategic Plan for Biodiversity 2011–2020, COP 10), with their focus on effective management systems supporting the conservation of biodiversity and eco-system services (Aichi Biodiversity Target 11). The aim of this paper is to illustrate the MEVAP (Monitoring and EValuation of Protected Areas) methodology, Italy's contribution to the topic of evaluating the effectiveness of protected areas within the international landscape (WDPA–IUCN, World Database on Protected Areas – Union for Conservation of Nature ). The purpose of MEVAP is to provide a periodical review procedure as part of the process to improve the management of protected areas. Its starting point is the analysis of qualitative and quantitative data pertinent to the environmental, social and economic aspects of protected areas and to their governance. This paper illustrates the results obtained using the MEVAP method and its application to several clusters of Italian national parks. While highlighting the potential of this method, the document also proposes an initial assessment of the environmental, social and economical performance of protected areas and how performance is connected to its governance. Underpinning the study is the need to expand the use of evaluation practices and to spur scientific debate in the direction of widely spread adaptive management methods, with a view to optimising policies and management procedures and, therefore, achieving the protection targets that must be met by protected areas through their institutions.